Komunikasi Ansietas dalam Proses Modality Switching Pada Pemain Mobile Legends Bang-Bang - Akbar, Muhammad Sayyid; Isnaini, Muhamad (Jurnal Riset Komunikasi (JURKOM), 2025)
Modality switching is a change of modality in the form of changing communication channels in e-sports, especially Mobile Legends Bang Bang (MLBB), modality switching can cause anxiety for players. The reason is the change in the way of playing that they usually fight online to fight offline in a tournament. The research was conducted using a qualitative approach with a case study method. The case taken is the MPL 2025 tournament. Data were obtained through field observations and interviews with a number of informants. The results show that MLBB pro players show a variety of anxieties communication that can be seen from face-to-face expressions such as smiles, glances, ways of communicating and how to play in the gameplay screen such as attacking strategies, defense and speed in fighting.